A New Triterpene Glycoside from the Sea Cucumber Holothuria Scabra Collected in Vietnam - Nguyen Van Thanh; Nguyen Hai Dang; Phan Van Kiem; Nguyen Xuan Cuong; Hoang Thanh Huong; Chau Van Minh (Universitas Gadjah Mada, 2006)
Bioassay guided fractionation led to the isolation of a new triterpene glycoside, holothurinogenin B (1) along with three known compounds, holothurin B (2), holothurin A (3), and holothurin A2 (4), from the methanol extract of the Vietnamese sea cucumber Holothuria scabra. Their structures were deduced from the spectral analysis (1D-NMR, 2D-NMR, MS) and chemical evidences.